Radar network warning system for the protection and sustainable development of the English-speaking Caribbean countries (WMO GenevaCH, 1994)
Outlines a project which seeks to mitigate the economic and social losses that might arise from adverse weather conditions in the region by provision of an advanced weather warning system, and to facilitate economic development by providing relevant weather data to weather sensitive industries in the countries covered by the radars. Identifies six countries in which the radars are to be cited viz. Guyana, Barbados, Antigua and Barbuda, Jamaica, Belize and Trinidad and Tobago.
DC